Festival-Based Arabic Curriculum Development: The Role of Arabic Storytelling in Strengthening Students’ Communicative Competence at PMDG Putri Campus 1 - Subakir, Fairuz; Agus Yasin; Ahmad Ario Sofian; Nur Fera Khalifah; Nuraeni Rahmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines the role of Arabic Storytelling in the Arabic Language Festival as a strategy for festival-based Arabic curriculum development at PMDG Putri Campus 1. The research aims to analyze how storytelling activities contribute to strengthening students’ communicative competence through experiential and performance-based learning. This study employed a qualitative case study design involving Arabic teachers, festival organizers, language supervisors, judges, and student participants. Data were collected through participatory observation, semi-structured interviews, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that Arabic Storytelling functioned not merely as an extracurricular competition but as a curriculum enrichment practice integrated into the pesantren’s communicative Arabic learning ecosystem. The activity strengthened students’ fluency, pronunciation accuracy, confidence, emotional expression, public speaking ability, and spontaneous interaction in Arabic. Furthermore, the festival contributed to strengthening *bi’ah lughawiyyah* by creating authentic and collaborative communicative environments beyond classroom instruction. The study concludes that festival-based language activities possess significant potential for developing communicative Arabic curricula through immersive and experiential learning practices. Theoretically, this study contributes to communicative Arabic pedagogy by introducing festival-based curriculum development as an alternative framework for strengthening communicative competence in Islamic boarding schools.